2017
DOI: 10.1016/j.cellsig.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin (OXT)-stimulated inhibition of Kir7.1 activity is through PIP 2 -dependent Ca 2+ response of the oxytocin receptor in the retinal pigment epithelium in vitro

Abstract: Oxytocin (OXT) is a neuropeptide that activates the oxytocin receptor (OXTR), a rhodopsin family G-protein coupled receptor. Our localization of OXTR to the retinal pigment epithelium (RPE), in close proximity to OXT in the adjacent photoreceptor neurons, leads us to propose that OXT plays an important role in RPE-retinal communication. An increase of RPE [Ca2+]i in response to OXT stimulation implies that the RPE may utilize oxytocinergic signaling as a mechanism by which it accomplishes some of its many role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
3
20
0
1
Order By: Relevance
“…First is through G α q -mediated activation of the phospholipase C, which by the action of inositol-triphosphate binding on inositol 1,4,5-trisphosphate receptor (IP 3 R) induces release of calcium from intracellular sources [ 38 ]. Second is through inhibition of the potassium Kir7.1 channels, which induces plasma membrane depolarization and calcium entry through the voltage-dependent calcium channel [ 39 , 40 ]. Another mechanism on how oxytocin may induce membrane depolarization on presynaptic membranes is through activation of Na + /Ca 2+ exchanger and the opening of a nonselective cation channel [ 41 ].…”
Section: Presynaptic Modulation By Oxytocinmentioning
confidence: 99%
“…First is through G α q -mediated activation of the phospholipase C, which by the action of inositol-triphosphate binding on inositol 1,4,5-trisphosphate receptor (IP 3 R) induces release of calcium from intracellular sources [ 38 ]. Second is through inhibition of the potassium Kir7.1 channels, which induces plasma membrane depolarization and calcium entry through the voltage-dependent calcium channel [ 39 , 40 ]. Another mechanism on how oxytocin may induce membrane depolarization on presynaptic membranes is through activation of Na + /Ca 2+ exchanger and the opening of a nonselective cation channel [ 41 ].…”
Section: Presynaptic Modulation By Oxytocinmentioning
confidence: 99%
“…Both the oxytocin receptor (17) and the MC4R (14) have been shown to regulate Kir7.1 function at the membrane in a physiologically relevant manner, with the former mediated via a PIP 2 intermediate. The mechanism(s) for regulation of Kir7.1 by MC4R remain to be determined, although the potential for Kir7.1 and MC4R to form complexes was shown by co-immunoprecipitation of tagged proteins from HEK293T cells (14).…”
Section: Gpcrs Differentially Regulate Kir71 Glycosylationmentioning
confidence: 99%
“…Moreover, within dendritic spines of cholinergic neurons, M1 receptor activation has been shown to lead to inhibition of Kir2.x channels through G q activation of phospholipase C, which depletes the second messenger phosphatidylinositol 4,5bisphosphate (PIP 2 ) that is needed for Kir channel function (16). Kir7.1 likewise has a PIP 2 dependence for activity and was recently shown in RPE cells to be regulated by the oxytocin G q -coupled GPCR, through phospholipase C-mediated inhibition (17). However, the MC4R-mediated closure of Kir7.1 was found to be independent of G proteins (14).…”
mentioning
confidence: 99%
“…A variety of extracellular stimuli acting on tyrosine kinase-associated receptors or G protein-coupled-receptors have been reported to stimulate release of inositol phosphates in cultured RPE cells, presumably derived from PLC action of PI(4,5)P 2 , on a timescale of tens of minutes; effective stimuli included fetal bovine serum, agonists for muscarinic, histamine, and serotonin, peptides, including bradykinin, arginine vasopressin, bombesin and oxytocin, [106][107][108][109]. The physiological relevance of these observations was not explored, but an in vivo study using frogs demonstrated dramatic acceleration of inositol phosphate release, especially of InsP 3 , following stimulation by light [21].…”
Section: Studies Of Pi Metabolism In the Rpementioning
confidence: 99%